2016
DOI: 10.1093/jxb/erw106
|View full text |Cite
|
Sign up to set email alerts
|

Plastid ribosomal protein S5 is involved in photosynthesis, plant development, and cold stress tolerance in Arabidopsis

Abstract: HighlightPlastid RPS5 affects proteins involved in photosynthesis and translation machinery and mediates cold stress tolerance in Arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…Furthermore, a relationship between photosynthesis and ribosomal machinery has been previously reported in Arabidopsis [61]. Thus, the decreased abundance of chloroplast 16S rRNA promoted by the lack of ribosomal protein S5 leads to the suppression of a great number of core components of PSI and PSII [61]. In summary, according to this study's findings, the pod maturation process in common bean leads to specific transcriptome changes that accelerate the breakdown of photosynthetic and ribosomal machinery.…”
Section: Pod Maturation Is Regulated At Translational Level and Involsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, a relationship between photosynthesis and ribosomal machinery has been previously reported in Arabidopsis [61]. Thus, the decreased abundance of chloroplast 16S rRNA promoted by the lack of ribosomal protein S5 leads to the suppression of a great number of core components of PSI and PSII [61]. In summary, according to this study's findings, the pod maturation process in common bean leads to specific transcriptome changes that accelerate the breakdown of photosynthetic and ribosomal machinery.…”
Section: Pod Maturation Is Regulated At Translational Level and Involsupporting
confidence: 69%
“…All these results corroborate that the significant reduction of photosynthesis, as part of the senescence developmental program, is a key step for pod maturation in common bean. Furthermore, a relationship between photosynthesis and ribosomal machinery has been previously reported in Arabidopsis [61]. Thus, the decreased abundance of chloroplast 16S rRNA promoted by the lack of ribosomal protein S5 leads to the suppression of a great number of core components of PSI and PSII [61].…”
Section: Pod Maturation Is Regulated At Translational Level and Involmentioning
confidence: 92%
“…Defects in plastid translational capacity are often associated with impaired acclimation to cold, as reported previously in mutants defective for PRPL33, PRPS5, or RDB1 (Rogalski et al, 2008;Wang et al, 2016;Zhang et al, 2016). Therefore, we quantified cold acclimation in both rh50-1 mutants and wild-type plants.…”
Section: Rh50 and Gun1: Coexpression And Colocalizationmentioning
confidence: 85%
“…Many mutants affected in plastid ribosomal activity are more sensitive to cold treatments than wildtype plants (Rogalski et al, 2008;Fleischmann et al, 2011;Wang et al, 2016;Zhang et al, 2016;Paieri et al, 2018). Experiments with plants grown for 2 weeks at 22°C and then transferred for 5 weeks to 4°C showed that both crass mutants were more susceptible to this treatment than wild-type plants or overexpressors of CRASS1:YFP in the crass-1 background (oeCRASS: YFP#1 crass-1; Fig.…”
Section: Crass Is Necessary For Tolerance To Cold Stressmentioning
confidence: 99%
“…For instance, loss of the 23S-4.5S maturation factor RH50 leads to erythromycin sensitivity and reduced chloroplast protein synthesis upon cold exposure (Paieri et al, 2018). Moreover, mutants for plastid ribosomal subunits (like PRPS5, PRPS6, and PRPL33) or the elongation factor SVR3 display reduced tolerance to cold stress (Rogalski et al, 2008;Liu et al, 2010;Zhang et al, 2016;Wang et al, 2017). Furthermore, the cytosolic pre-18S rRNA processing factor RH7 is involved in cold tolerance (Huang et al, 2016), providing a general link between temperature on the one hand and translation or ribosome biogenesis on the other.…”
Section: Crass Becomes Critical For Translation Only Under Certain Comentioning
confidence: 99%